Atividade antibacteriana e antioxidante de óleos essenciais de limão tahiti (Citrus latifolia), limão siciliano (Citrus limon), anis estrelado (Illicium verum) e alecrim (Rosmarinus officinalis) - Pereira, Marcus Vinicius (2016)
In the search for safer foods arises the need to use less toxic additives. Essential oils are receiving special attention because of its antioxidant and antimicrobial properties and their natural origin. Nevertheless, one should also take into account the toxicity and organoleptic properties of the chosen essential oils. This paper evaluates the antibacterial and antioxidant properties of commercial essential oils of lime (Citrus latifolia), lemon (Citrus limon), star anise (Illicium verum) and rosemary (Rosmarinus officinalis). The antibacterial activity was observed by the microdilution method using 96 wells microtiter plates. The antioxidant activity was conducted by the scavenging of DPPH radical (2,2-diphenyl-1-picrylhydrazyl) and Ferric Reducing Antioxidant Power (FRAP) methods. The lime essential oil showed the highest antioxidant activity with an IC50 of 264.16 mg.mL-1 followed by the essential oil of star anise and lemon (IC50 of 330.30 and 395.45 mg.mL-1, respectively) rosemary essential oil did not show any antioxidant activity in both methods. By the FRAP method, the star anise essential oil showed the highest activity following the lemon and then lime. None of the essential oils showed antibacterial activity at concentrations equal to or less than 20 mg.mL-1 against strains of Escherichia coli, Staphylococcus aureus, Salmonella typhi and Bacillus cereus. The results indicate that the chosen essential oils do not present applicability as a food additive and scavenger of radicals, that can be explained by the absence of phenolic compounds in the composition thereof.